DETERMINAN STATUS GIZI PADA SISWA SEKOLAH DASAR - Ufairatul ulaiya , Ufairatul ulaiya; Nurdin, Ambia; Fitria, Ully; Dinen, Kiki Asrifa (Teewan Journal Solutions, 2024)
Malnutrition remains a central issue. There are various factors that cause this problem to become very complex. The research problem is what factors are related to nutritional status. The aim of the research was to determine factors related to nutritional status in children in grades 4, 5, and 6 at elementary school 02 Ngesrep Banyumanik, Semarang. Survey research methods, By using a cross section approach. The population is 64 students. Purposive sampling technique was used to obtain a sample of 62 people. Data collection techniques are carried out by interviews, Observation and documentation, Meanwhile, nutritional status data is carried out using anthropometric measurements. Data analysis was carried out by universities and bivariate using the chi square test. The research results show related factors With nutritional status is the mother's level of knowledge (p=0.0001), mother's education (p=0.0001), family income (p=0.0001), Infectious diseases (p=0.0001), level of energy consumption (p=0.0001), level of protein consumption (p=0.0001). Factors that were not related to nutritional status were number of family members (p=0.074). Research conclusions, variables related to nutritional status are mother's level of knowledge, mother's education, family income, infectious diseases, energy consumption level, And the level of protein consumption.